Sequential O-Arylation/Lanthanide(III)-Catalyzed [3,3]-Sigmatropic Rearrangement of Bromo-Substituted Allylic Alcohols - Ramadhar, Timothy R.; Kawakami, Jun-ichi; Batey, Robert A. (Synlett, 2017)
Lanthanide(III)-catalyzed aryl-Claisen rearrangement of substrates bearing halo-substituted allyl groups, specifically 2-bromoallyl aryl ethers, afford ortho-2-bromoallylphenols. Aryl ether substrates were synthesized from brominated allylic alcohols via Mitsunobu reaction, Cu(II)-catalyzed arylation using potassium aryltrifluoroborate salts, or SNAr reaction. Aryl-Claisen rearrangements proceeded in moderate to excellent yields using Eu(III) catalysis. The alkenylbromide functionality remains intact, illustrating the compatibility of synthetically important alkenylhalides during C–O/C–C σ-bond migration processes. Subsequent derivatization of the ortho-2-bromoallylphenol products through O-alkylation or C-arylation/alkenylation via Suzuki–Miyaura cross-coupling demonstrate the potential to access densely-functionalized molecules.
Keywords: aryl-Claisen [3,3]-sigmatropic rearrangement; alkenylbromide; arylation; organotrifluoroborate salt; lanthanide catalysis; phenols; Suzuki–Miyaura reaction; Chan–Lam–Evans arylation